A calculation method of interior ballistic two-phase flow considering the recoil of gun barrel. (25th February 2021) - Dong, Xiaoli; Rui, Xiaoting; Li, Chao; Wang, Yan; Fan, Lili
Highlights: The theory of interior ballistic two-phase flow is combined with the transfer matrix method of multibody system. A calculation method of interior ballistic two-phase flow considering the gun barrel recoil is proposed. The launch process of a self-propelled gun is simulated. The effects of the barrel recoil on the interior ballistic process are discussed in depth. Abstract: The theory of interior ballistic two-phase flow (IBTPF) is the primary means to study the distributions of physical quantities in gun chamber. In previous calculations, the gun breech is usually simplified as a fixed wall boundary, totally ignoring the effect of gun barrel recoil on interior ballistic processes. Thus to truly describe the interior ballistic process of the self-propelled gun (SPG), the transfer matrix method of multibody system (MSTMM) is combined with the theory of IBTPF in this paper. By simultaneously solving the generalized coordinate equations of multibody system and the conservation equations of IBTPF, the gun barrel recoil is converted to the moving boundary of the gun breech, and a more accurate calculation method of IBTPF is established. The results show that the simulated vibration characteristics, dynamic response during launch as well as interior ballistic performance of the SPG are all in good agreement with test values. Compared with no recoil, the gun barrel motion affects the growth regularity of the chamber volume behind the projectile, and eventually results in the changes of interior ballistic performance indexes such as maximum breech pressure and muzzle velocity. Overall, this study provides a more accurate prediction and simulation tool to enable better insight into such complicated interior ballistic processes, which is of great significance to the launch safety analysis and subsequent ballistic calculations.